2017
DOI: 10.12783/dtetr/sste2016/6604
|View full text |Cite
|
Sign up to set email alerts
|

Hotel Frontline Employee’s Affective Commitment and Service Creativity: the Mediating Effect of Emotional Labor

Abstract: Abstract. According to the investigation of three star hotels' employees and 108 effective questionnaires, we study the relationship between the affective commitment and service creativity of employees and the mediating effect of emotional labor. The results showed that affective commitment has a significant positive relationship with emotional labor and employees' service creativity; and emotional labor has a significant positive influence on the service creativity; deep acting plays a part of the mediating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…To see the complete license contents, please visit http://creativecommons.org/licenses/by-nc/4.0/ highly needed by universities (Hirst et al, 2015;Gong, Huang, & Farh, 2009;Montani, Courcy, & Vandenberghe, 2017). This results are consistent with the results of Cheung (2005) and Shi and Su (2017). However, the findings show different results from Moss and Ritossa findings (2007), which revealed that affective commitment does not significantly affect creativity.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…To see the complete license contents, please visit http://creativecommons.org/licenses/by-nc/4.0/ highly needed by universities (Hirst et al, 2015;Gong, Huang, & Farh, 2009;Montani, Courcy, & Vandenberghe, 2017). This results are consistent with the results of Cheung (2005) and Shi and Su (2017). However, the findings show different results from Moss and Ritossa findings (2007), which revealed that affective commitment does not significantly affect creativity.…”
Section: Resultssupporting
confidence: 85%
“…Since creativity cultivated from new ideas and outlooks, consequently individual network to pursue advice also influences the extent of employee openness to fresh and miscellaneous information, and their chance to produce creative ideas (Gong, Huang, & Farh, 2009). A positive relationship was found between affective commitment with creative work behavior (Shi & Su, 2017). From the explanation above, we propose the following hypothesis: H3: Affective commitment significantly influences creativity.…”
Section: Affective Commitment and Creativitymentioning
confidence: 91%
See 2 more Smart Citations